2008
DOI: 10.1016/j.abb.2008.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Brefeldin A inhibits cholesterol efflux without affecting the rate of cellular uptake and re-secretion of apolipoprotein A-I in adipocytes

Abstract: A possible role of cellular uptake and re-secretion of apoA-I in the mechanism of cholesterol efflux induced by apoA-I was investigated using a novel experimental approach. Incubation of adipocytes with a recombinant human apoA-I containing a consensus PKA phosphorylation site, pka-ApoA-I, leads to the appearance of phosphorylated protein in the cell culture medium unambiguously proving cellular uptake and re-secretion of pka-ApoA-I. Phosphorylation of apoA-I is abolished by PKA inhibitors and enhanced by PKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…The exposure of cells to high concentrations of β-CD (10-100 mM) results in rates of cholesterol efflux far in excess of those achieved with physiological cholesterol acceptors such as HDL. The selection of BFA as an inhibitor was based on the fact that it strongly suppresses the HDL/apo mediated cholesterol efflux from cholesterol-enriched cells and it has been shown to affect intracellular trafficking of ABCA1 (30). Consistent with previous studies, the present study has demonstrated that treatment of cells with cholesterol acceptor β-CD promoted cholesterol efflux and reduced the rate of ox-LDL-induced apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…The exposure of cells to high concentrations of β-CD (10-100 mM) results in rates of cholesterol efflux far in excess of those achieved with physiological cholesterol acceptors such as HDL. The selection of BFA as an inhibitor was based on the fact that it strongly suppresses the HDL/apo mediated cholesterol efflux from cholesterol-enriched cells and it has been shown to affect intracellular trafficking of ABCA1 (30). Consistent with previous studies, the present study has demonstrated that treatment of cells with cholesterol acceptor β-CD promoted cholesterol efflux and reduced the rate of ox-LDL-induced apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…The method used to monitor apoA-I recycling was based on the use of a recombinant apoA-I (pka-apoA-I) that contains a consensus phosphorylation site for protein kinase A, PKA. Incubation of pka-apoA-I with adipocytes leads to the appearance of phosphorylated apoA-I in the cell culture medium indicating that the protein entered the cell, was phosphorylated by PKA, and then re-secreted [26]. The ability of the method to monitor actual apolipoprotein recycling was strongly supported in the previous study.…”
Section: Introductionmentioning
confidence: 81%
“…Using a novel method to monitor apoA-I uptake and re-secretion (apoA-I recycling), we have recently reported apoA-I recycling by adipocytes [26]. We have also shown that lipidation of apoA-I can be effectively inhibited by BFA, which affects intracellular vesicular and ABCA1 transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant apoA-I was cloned and purified as previously described was used to initiate cellular lipid efflux [29]. At the start of the experiment, fresh 0.05% BSA–DMEM (to determine background levels of efflux) or 0.05%BSA–DMEM containing 75 µg/ml apoA-I was added to the cells.…”
Section: Methodsmentioning
confidence: 99%